MMP-9 expression in rat pup incisor teeth is not altered by maternal hypertension or maternal atenolol treatment during pregnancy and lactation - Elias, Gracieli Prado (2025)
Hypertension alters tooth formation and Atenolol reduces the blood pressure of spontaneously hypertensive rats (SHR) during pregnancy and lactation, and as demonstrated before, increases the microhardness of the SHR offspring’s teeth. MMP-9 is overexpressed in different tissues of hypertensive animals and treatment of hypertension substances can reverse this alteration. We hypothesize hypertension alters the expression of MMP-9 in dental structures of SHR offspring and that treating female SHR with atenolol prevents this alteration. This study aimed to evaluate the expression of matrix metalloproteinase (MMP-9) in incisor teeth (IT) in male offspring of SHR (30 days old) treated or untreated with Atenolol during pregnancy and lactation. MMP-9 expression was evaluated in ameloblasts (AM), enamel matrix (EM), odontoblasts (OD), and predentin (PD) of IT through immunohistochemical reactions (immunoperoxidase). Data were analyzed by Shapiro-Wilk and Kruskal-Wallis (p < 0.05), with Dunn post-test. Histological differences were not observed between IT tissues of SHR and normotensive Wistar rats. For the first time, our data showed that MMP-9 expression in specific dental structures is not altered in SHR. Atenolol treatment increased MMP-9 immunostaining in EM of Wistar rat, however, Atenolol did not alter MMP-9 in the IT tissues of SHR. Our results demonstrated that MMP-9 expression in dental tissues is not affected by hypertension or atenolol treatment in dental tissues. If confirmed in humans, the results obtained in this study will corroborate the suggestion that MMP-9 is not a viable therapeutic target for the treatment of dental alterations associated with maternal hypertension.